PENGARUH HEAT INPUT PADA PENGELASAN COMBINE GTAW-SMAW DISSIMILLAR MATERIAL BAJA AISI 1045 DENGAN SS 304 TERHADAP SIFAT MEKANIK - Fauzi, Yusuf Rizal; Heka, Akbar Ela (Machine : Jurnal Teknik Mesin, 2024)
The growth and development of technology in the construction sector which is increasingly advanced and rapid, cannot be separated from the process of joining similar metals or joining dissimilar metals. This dissimilar welding uses AISI 1045 stainless steel and SS 304 carbon steel with a size of 200 x 200 x 6 mm. The welding method uses GTAW with ER 309 L filler metal with a diameter of 2.4 mm. Dissimilar welding aims to understand the mechanical properties affected by heat input. This study varies the heat input of 1.08 kJ / mm and heat input of 0.83 kJ / mm. The tests carried out were microstructure observations, tensile tests and hardness tests. The results of the tensile test all fractures occurred in the SS 304 base metal with an average value of 886 MPa. The results of the hardness test showed that the fusion line point had a higher hardness value compared to the base metal. In the observation of the microstructure of the SS 304 fusion line area, it has ferrite and pearlite phases, for the weld metal area it has ferrite, austenite and dendritic phases, in the AISI 304 fusion line section it has ferrite and austenite phases. The effect of heat input can be concluded that heat input affects the HAZ and fusion line due to the increasing hardness value.